Monitoring Gaseous CO2 and Ethanol above Champagne Glasses: Flute versus Coupe, and the Role of Temperature - Liger-Belair, Gérard; Bourget, Marielle; Pron, Hervé; Polidori, Guillaume; Cilindre, Clara (PLOS ONE, 2012)
In champagne tasting, gaseous CO2 and volatile organic compounds progressively invade the headspace above glasses, thus progressively modifying the chemical space perceived by the consumer. Simultaneous quantification of gaseous CO2 and ethanol was monitored through micro-gas chromatography (μGC), all along the first 15 minutes following pouring, depending on whether a volume of 100 mL of champagne was served into a flute or into a coupe. The concentration of gaseous CO2 was found to be significantly higher above the flute than above the coupe. Moreover, a recently developed gaseous CO2 visualization technique based on infrared imaging was performed, thus confirming this tendency. The influence of champagne temperature was also tested. As could have been expected, lowering the temperature of champagne was found to decrease ethanol vapor concentrations in the headspace of a glass. Nevertheless, and quite surprisingly, this temperature decrease had no impact on the level of gaseous CO2 found above the glass. Those results were discussed on the basis of a multiparameter model which describes fluxes of gaseous CO2 escaping the liquid phase into the form of bubbles.